2017
DOI: 10.12816/0040617
|View full text |Cite
|
Sign up to set email alerts
|

Value of Glycosylated Hemoglobin at 34 Weeks Gestation in the Prediction of Adverse Neonatal Outcome

Abstract: Background: Gestational diabetes is diabetes, or high blood sugar levels, that develops during pregnancy. It occurs in about 4% of all pregnancies. It is usually diagnosed in the later stages of pregnancy and often occurs in women who have no prior history of diabetes. Aim of the Work: To assess the predictive value of elevated glycosylated hemoglobin at 34 weeks' gestation with adverse fetal outcome as regard fetal macrosomia and neonatal hypoglycemia. Patients and Methods: This prospective longitudinal cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Contrary to the study, Hassan Khairy et al in their study in GDM patients showed that the incidence of neonatal hypolycemia and RDS were significantly higher when the HbA1c level were raised with the cut offs of HbA1c levels taken as > 7.9%. 24 Similarly study done by Sen Gupta et al in patients with pregestational diabetes/GDM showed statistically significant higher incidence of hypoglycemia, hyperbilirubinemia and respiratory distress syndrome when the HbA1c levels were >6% in 2 nd and 3 rd trimester. 16…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Contrary to the study, Hassan Khairy et al in their study in GDM patients showed that the incidence of neonatal hypolycemia and RDS were significantly higher when the HbA1c level were raised with the cut offs of HbA1c levels taken as > 7.9%. 24 Similarly study done by Sen Gupta et al in patients with pregestational diabetes/GDM showed statistically significant higher incidence of hypoglycemia, hyperbilirubinemia and respiratory distress syndrome when the HbA1c levels were >6% in 2 nd and 3 rd trimester. 16…”
Section: Discussionmentioning
confidence: 79%
“…17,19 Hassan Khairy et al also showed similar results in their study that high HbA1c levels in third trimester are good predictor of macrosomia in pregnancy with GDM. 24 In the study, of the total Large for gestational baby, 39.5% of the babies were born to mother who had euglycemic control (as per their fasting and blood sugar levels) but with HbA1c level ≥ 5.8%, indicating HbA1c level is a better marker for predicting large for gestational age babies in third trimester.…”
Section: Discussionmentioning
confidence: 93%